Activities for Developing Communicative Competence in Grade 9 English Modules - Molines-Balleta, Faeona Ferna Joyce (International Journal of Research in Interdisciplinary Studies, 2025)
The use of modules in teaching aims to develop communicative competence—the core goal of English language learning, however, current modules often place excessive emphasis on grammar and fall short in providing engaging, authentic tasks. This study aimed to analyze tasks and activities according to classification of task types, categorization of mode of communication and aspects of communicative competence. This study analyzed the tasks and activities in the Grade 9 English Modules using content analysis design, through CEFR modes of communication, and communicative competence categories. Findings showed that reading and writing were emphasized, while speaking was minimal and listening absent. Linguistic competence was most addressed; sociolinguistic and strategic competences were least. The study highlights an imbalance in macro skill integration and communicative competence in the modules. To foster well-rounded communicative competence, future modules should include more listening and speaking activities, collaborative tasks, and a stronger focus on sociolinguistic and strategic skills.